Managing personnel and human resources : strategies and programs - Heneman, Herbert Gerhard; Schwab, Donald P. (Homewood, Ill. : Dow Jones-Irwin, 1981)
This book is about the management of personnel in organizations. This entails analyzing individuals and jobs and assessing employees on outcomes such as performance and satisfaction, planning, external staffing, internal staffing and employee development, compensation, safety and health, and hours of work. This book is intended for human resource managers at all levels, as well as for line managers who wish to enhance their knowledge of this very important responsibility.
"Portions of this book were previously published ... under title Personnel/human resource management"--p. [iv]
Includes bibliographical references and index.
ne 17/07/2018
Loan
Keywords: Personnel management